Analysis of Gojek's Brand Perception Utilizing Twitter Hashtag: Sentiment Analysis Using Ekman's Classification - Wahyudi, Aditio; Arief Tirtana; Lady Diana Langoy (HM Publisher, 2023)
Advertisers constantly try to use different communication channels to approach consumers more effectively and promptly and increase their products' visibility and attractiveness. Gojek, an Indonesian ride-hailing and delivery company, uses hashtags as part of its marketing strategy on social media platforms such as Twitter and Instagram. This research aimed to analyze Gojek's brand perception using the Twitter hashtag. This research uses descriptive analysis and sentiment analysis using Ekman's classification of emotional expression algorithm. This research analyzed 813 tweets containing hashtags related to Gojek, an Indonesian ride-hailing and delivery company, including #AmanBersamaGojek, #Cerdikiawan, #JalanTerus, #PastiAdaJalan, and #SebelumGojek, to understand the sentiment and emotional tone of the tweets. Using Ekman's classification method for identifying and categorizing emotional expressions, the analysis found that the tweets were predominantly positive in sentiment, with surprise and joy being the most frequently expressed emotions. However, the research also identified a range of other emotions expressed in the tweets, including fear, sadness, disgust, and anger, indicating that Twitter users may have more complex and nuanced attitudes toward Gojek and its hashtags. In conclusion, Gojek may consider conducting additional research and implementing strategies to address negative emotions and better engage with its audience on social media to improve its brand perception on Twitter.